Respuesta :

Answer: A and C

Explanation:
The factor for A is x(x-5)(x+2)

The factor for C is (x-5)(x+2)(x+1)

The polynomials that have (x+2) as a factor are [tex]\rm A(x) = x^3-3x^2-10x[/tex] and [tex]\rm C(x) = x^3-2x^2-13x-10[/tex] and this can be determined by using the factorization method.

Check all the options in order to determine the polynomials that have (x+2) as a factor.

A)

[tex]\rm A(x) = x^3-3x^2-10x[/tex]

Factorize the above equation.

[tex]\rm A(x) = x(x^2-3x-10)[/tex]

[tex]\rm A(x) = x(x^2-5x+2x-10)[/tex]

[tex]\rm A(x) = x(x(x-5)+2(x-5))[/tex]

[tex]\rm A(x) = (x)(x+2)(x-5)[/tex]

This polynomial has a factor (x+2). Therefore, this option is correct.

B)

[tex]\rm B(x) = x^3+5x^2+4x[/tex]

Factorize the above equation.

[tex]\rm B(x) = x(x^2+5x+4)[/tex]

[tex]\rm B(x) = x(x^2+4x+x+4)[/tex]

[tex]\rm B(x) = x(x(x+4)+1(x+4))[/tex]

[tex]\rm B(x) = (x)(x+1)(x+4)[/tex]

Therefore, this option is incorrect.

C)

[tex]\rm C(x) = x^3-2x^2-13x-10[/tex]

Factorize the above equation.  

[tex]\rm C(x) = x^3+2x^2-4x^2-8x-5x-10[/tex]

[tex]\rm C(x) = x^2(x+2)-4x(x+2)-5(x+2)[/tex]

[tex]\rm C(x) = (x^2-4x-5)(x+2)[/tex]

This polynomial has a factor (x+2). Therefore, this option is correct.

D)

[tex]\rm D(x) = x^3-6x^2+11x-6[/tex]

Factorize the above equation.  

[tex]\rm D(x) = x^3+2x^2-8x^2-16x+27x+54-60[/tex]

In the above polynomial (x+2) is not the factor. Therefore, this option is incorrect.

For more information, refer to the link given below:

https://brainly.com/question/6810544

ACCESS MORE